SODES: Solving ordinary differential equations step by step - Galán-García, José Luis; Rodríguez-Cielos, Pedro; Galán-García, María Ángeles; Le Goff, Morgan; Padilla-Domínguez, Yolanda Carmen; Rodríguez-Padilla, Pablo; Atencia-McKillop, Iván; Aguilera-Venegas, Gabriel (Elsevier, 2023)
In this paper, we introduce SODES (Stepwise Ordinary Differential Equations Solver) a new solver for Ordinary Differential Equations (ODE). SODES can optionally provide the solution displaying all the steps needed to obtain it. This way, SODES is an important tool not only for researchers who need solving ODE but also constitutes an important tool for the teaching and learning process of ODE. SODES has been developed using programming with a Computer Algebra System (CAS). Specifically, we use the CAS Derive but it can be easily adapted to any other CAS supporting programming. SODES provides, step by step, the solution of the following types of ODE: separable, homogeneous, exact, integrating factors, linear, Bernoulli, Riccati, first order ODE of nth degree, Cauchy’s problems of first order ODE, higher order linear homogeneous equations with constant coefficients, Lagrange’s method for particular solutions of higher order linear equations with constant coefficients, higher order linear equations with constant coefficients and Cauchy’s problems of higher order linear equations with constant coefficients. SODES also deals with two generic programs which determine the type or types of a given ODE and provides the solution. In this paper we will also introduce a draft of a Graphical User Interface (GUI) for SODES in a local web application using programming in Python (using its CAS module SymPy) which is a more portable and free CAS. This draft can be used in English, French and Spanish, and can be easily extended to other languages. The code of SODES and the GUI are freely available so that it can be used by users who also will be able to adapt it to their needs
Keywords: Ecuaciones diferenciales; Análisis matemático; Ordinary Differential Equations (ODE); ODE solvers; Computer Algebra Systems (CAS); Programming with CAS; Stepwise solutions